Integrated filter antenna (vivaldi) for microwave applications - Amalina, Binti Affendi. (Universiti Malaysia Sarawak (UNIMAS), 2017)
Antenna and filter are both the important components involved in microwave system. Antenna is used as a receiver or transmitter in microwave transmission system. As for filter, it acts to receive or reject any frequencies that don‟t fall within the required range or bands. For instance, a bandpass filter would pass signals or frequencies only in a certain range or band while attenuating any signals outside this range. Usually, antenna and filter are connected separately. However, this connection would result in impedance mismatch that would affect the whole performance of the system. In order to overcome this problem, an integrated filtering antenna design is proposed. In this research, this design would benefit so much in terms of miniaturization and it is also low cost. These two factors are in great demands for RF receiver front ends. The idea of integrating this filtering antenna into a single component will reduce the size of the system and also enhance the performance of the system. In this project, the proposed design of antipodal Vivaldi antenna is to be integrated with an Open-Loop Resonator Bandpass Filter (OLR BPF). The structure will be designed on an FR4 substrate with a thickness of 1.6 mm and a permittivity, of 4.7 mm. There are two ways to implement the integrating of this filtering antenna; which are the cascaded method and co-design method.